Practical guidelines for reproducible N2O flux chamber measurements in nutrient-poor ecosystems - N. Y. Triches; N. Y. Triches; J. Engel; A. Bolek; T. Vesala; M. E. Marushchak; A.-M. Virkkala; M. Heimann; M. Göckede (Atmospheric Measurement Techniques)
The atmospheric concentration of nitrous oxide (N2O) has increased significantly since 1800, mainly due to agricultural activities. However, due to their large area, nutrient-poor natural soils, including those in the (sub-) Arctic, also play a crucial role in N2O emissions and consumption. Despite their importance, these soils have been understudied, due to methodological limitations in detecting low fluxes. Our study addresses this knowledge gap by testing a fast-responding portable gas analyser (PGA; Aeris MIRA Ultra N2O/CO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="50pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1198afae3fddbeac3f158918b70874bb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-3407-2025-ie00001.svg" width="50pt" height="14pt" src="amt-18-3407-2025-ie00001.png"/></svg:svg>) combined with manual chambers (height and diameter: 25 cm) for measuring N2O fluxes from a nutrient-poor, sub-Arctic peatland. Our results show that this setup can detect and quantify low N2O flux rates, with a mean and standard error of -0.61±0.08<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="0f4baef41c35e0eea360c1f54aff0e6d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-3407-2025-ie00002.svg" width="64pt" height="10pt" src="amt-18-3407-2025-ie00002.png"/></svg:svg> µg N2O-N m-2<mspace linebreak="nobreak" width="0.125em"/>h-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="39pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="7d5f1ff3744b20a3bbdaae9d67d679c1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-3407-2025-ie00003.svg" width="39pt" height="13pt" src="amt-18-3407-2025-ie00003.png"/></svg:svg> for a 5 min closure time, as observed in our study. More than 70 % of the measured N2O fluxes exceeded the minimum detectable flux (0.027±0.0002<mspace width="0.125em" linebreak="nobreak"/>µmol<mspace linebreak="nobreak" width="0.125em"/>m-2<mspace width="0.125em" linebreak="nobreak"/>h-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="138pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="cf70b445337f7eb6552e485c9b4d1631"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-3407-2025-ie00004.svg" width="138pt" height="15pt" src="amt-18-3407-2025-ie00004.png"/></svg:svg>), which varied according to chamber closure time. Our study highlights the importance of using fast-responding analysers to measure low N2O fluxes and improve our understanding of diverse N2O flux dynamics. For nutrient-poor soils, we recommend a chamber closure time of approximately 5 min. We also found that a non-linear flux calculation model yielded better results and was broadly applicable, including cases where data were linearly distributed. Overall, our study demonstrates the potential of fast-responding analysers to improve our understanding of N2O flux dynamics in nutrient-poor soils.